ANALYSIS OF LACTATE RECOVERY CURVE AFTER TABATA PROTOCOL ON CYCLING (Fiep Bulletin - online, 2017)
The aim of the study was to verify the return curve of lactate to baseline levels after a session of the Tabata protocolwith a stationary bike roller. Therefore Ten male cyclists (30.95 ±6.46 years, 80.07 ±9.04 kg; 177.1 ±6.84 cm) were submitted toeight maximum intensity of 20s series, 10s active recovery there between. Venous blood collected the day before the test,pretest, posttest, after 1h, 12h, 24h, 48h, and 72h characterized the study design. There was a significant difference (p